Gardella, Mariana. “El testimonio de Aristóteles sobre Zenón de Elea como un detractor de ‘lo uno’.” (2016)
Gardella, Mariana. “El testimonio de Aristóteles sobre Zenón de Elea como un detractor de ‘lo uno’.” Eidos 23 (2015): 157-181.